Highly sensitive and selective turn-on fluorescent probes for Cu2+ based on rhodamine B. Issue 26 (8th June 2015) - Yuan, Ye; Sun, Shiguo; Liu, Si; Song, Xinwei; Peng, Xiaojun
Abstract : A new rhodamine B-based fluorescent probe RL for Cu 2+ has been designed, synthesized, and characterized. Abstract : A new rhodamine B-based fluorescent probe RL for Cu 2+ has been designed, synthesized, and characterized. It exhibits a very high selectivity and sensitivity for the detection of Cu 2+ in CH3 CN : H2 O = 1 : 9 (v/v) buffered with Britton–Robinson (pH = 7.02), the detection limit can reach 0.739 nM, which is the lowest reported. Furthermore, the probe RL can be made into test papers to detect the cupric ions in drinking water by the naked eye. RL can also be used for imaging Cu 2+ in living cells and is almost non-toxic.